RESCUE OF INFLAMMATORY RENAL DAMAGE BY MEDICINAL PLANT EXTRACTS IN DIABETIC RATS: Life Science-Biochemistry - SADDIQ, AMNA A; AZZA. M. MOHAMED (International Journal of Life Science and Pharma Research, 2019)
Diabetic nephropathy (DN) is the most critical diabetic complication that leads to renal failure. The purpose of this research was to explore the anti-diabetic effectiveness of Cucumis melo var. flexuosus and/or Phoenix dactylifera fruit aqueous extracts and their mechanisms in alleviating nephropathy in hyperglycemic rats. Diabetes was promoted in rats by injection (i.p.) of a single dose of streptozotocin (STZ). C. flexuosus and P. dactylifera extracts (CFE and PDE respectively) were ingested to diabetic rats for thirty consecutive days. The data revealed that intake of either plant extract or their combination to diabetic rats, significantly diminished the serum glucose and raised the serum insulin concentration. The plant extracts significantly ameliorated the increases in relative kidney weights as well as in renal tumor necrosis factor (TNF-α), serum C –reactive protein (CRP) and renal vascular endothelial factor (VEGF). Serum kidney function markers (creatinine, uric acid and urea) were also decreased in diabetic rats treated with the plant extracts. Histopathological observation was also carried out to confirm the biochemical results. This study has proven that the current plant extracts have potential hypoglycemic effect and could attenuate diabetic inflammatory renal damage in rats. The combination of the two extracts was synergistically the effective one. This result may help in exploring a novel therapy to manage diabetes and its complications.